Al-Ḥaqīqah al-Muwāfaqah li al-Sharī‘ah: al-Taṣāluḥ bayn al-Taṣawuf wa al-Sharī‘ah bi Nusantara fi al-Qarn al-Sādis ‘Ashr al-Mīlādī - Iin Suryaningsih (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2013)
This article discusses the reinterpretation of waḥdat al-wujūd doctrine among Muslims of the archipelago, using the sharī‘ah approach in Sufism as suggested by Al-Būrhanpūrī (d.1620) in his work al-Haqīqah al-Muwāfaqah li al-Sharī‘ah. This work is one of the commentaries (sharḥ) from al-Tuḥfah al-Mursalah ila rūḥ al-Nabī SAW, that invited much debate among Muslims of the archipelago. Al-Būrhanpūrī’s detailed interpretation of waḥdat al-wujūd doctrine proved that the essence of the concept did not contradict the basic principles of Islam as contained in the Quran and Hadith. Al-Būrhanpūrī interpreted the concept through explanations that adjusted to the audience’s competence, utilizing oral language carefully in revealing spiritual experience not easily explained, as well as employing the bases of sharī‘ah. Al-Haqīqah al-Muwāfaqah has provided the information about the explanations of interpretation tradition among the archipelago sufis.DOI: 10.15408/sdi.v20i1.350